18F-Florbetaben Amyloid PET Imaging: A Chinese Study in Cognitive Normal Controls, Mild Cognitive Impairment, and Alzheimer’s Disease Patients - Chang, Yan; Li, Can; Yang, Hui; Wu, Yue; Xu, Baixuan; Zhang, Jinming; Wang, Ruimin (Frontiers in Neuroscience, 2020)
Objective To evaluate amyloid-β deposition with 18F-florbetaben (FBB) PET imaging against 11C-PIB PET in cognitive normal controls (NC), mild cognitive impairment (MCI), and Alzheimer’s disease (AD) patients. Methods We recruited 45 subjects (15 in each group of NC, MCI, and mild/moderate AD) who had undergone dynamic 18F-FBB amyloid PET imaging. For comparison study, 17 participants, including six NC, five MCI, and six AD patients, also underwent 11C-PIB PET imaging on separate days. Standardized uptake value ratios (SUVR) were calculated using the cerebellar cortex as the reference region with regions of interest (ROI) manually defined on co-registered CT. Quantitative analysis of mean cortical uptake was calculated using global SUVR. Spearman correlation analysis between MMSE scores and SUVR of 18F-FBB and 11C-PIB images were calculated. Results One (7%) of the 15 NC participants, nine (60%) of 15 MCI patients, and 12 (80%) of 15 AD patients had amyloid-positive lesions on 18F-FBB PET images. In AD patients, global SUVR was significantly higher than those of MCI patients (1.73 ± 0.62 vs. 1.55 ± 0.11, P < 0.001) and NC subjects (1.73 ± 0.62 vs. 1.13 ± 0.43, P < 0.001). In the comparison study, one NC participant, five MCI patients, and five AD patients had amyloid-positive lesions on 11C-PIB PET images. There was a significant linear correlation (r2 = 0.81, P < 0.001) between 18F-FBB and PIB global SUVR values. MMSE scores had negative correlations with SUVR on 11C-PIB PET (r1 = –0.650, P = 0.005) or SUVR on 18F-FBB PET (r2 = –0.754, P < 0.0001). Conclusion Our study suggests that 18F-FBB is a useful tracer for the evaluation of amyloid-β deposition in vivo and that global SUVR of 18F-FBB PET might be a reliable tool in the diagnosis of AD.